PENELITIAN PAJAK DAERAH: STUDI BIBLIOGRAFI 27 TAHUN - Erfandi, Moh.; Lastanti, Nadila; Aniyah, Shofinatul; Wati, Nova Dwi Medya; Herawati, Nurul (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya, 2024)
This research examines tax research, with the theme of regional taxes as an indicator of the development of tax science in Indonesia. Regional taxes are managed by provinces and districts/cities. Regional taxes are a contribution to regional original income, where regional taxes influence government administration activities and regional buildings. This research uses a sample of 194 articles published in SINTA 1 and 2 accredited journals. This research classifies them based on research topics and methods. The observation period used is 1997 – 2023. The research results show that the most researched topic is economics. Regional tax research is dominated by a quantitative paradigm. This research also found that 1997 was the first year that regional tax articles were published in SINTA 1 and 2 accredited journals. The implication of this research is to provide insight into the development of regional tax research in Indonesia over a period of 27 years and contribute to the accounting literature for understanding aspects of taxation. Apart from that, regional tax research is still open to further research using a qualitative paradigm and research topics that are still rarely researched.